2012
DOI: 10.1128/jb.00350-12
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of the Serotype k Streptococcus mutans Strain LJ23

Abstract: e Streptococcus mutans is the major pathogen of dental caries and occasionally causes infective endocarditis. Here we report the complete genome sequence of serotype k S. mutans strain LJ23, which was recently isolated from the oral cavity of a Japanese patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…The function of this TCS in S. mutans has yet to be determined. However, a recently sequenced serotype k strain (LJ23) also contains TCS-15 [73]. In our analysis of the genomes of the 57 isolates from across the globe, TCS-15 was found in 16 of the 57 strains, and was distributed across all serotypes.…”
Section: Resultsmentioning
confidence: 83%
“…The function of this TCS in S. mutans has yet to be determined. However, a recently sequenced serotype k strain (LJ23) also contains TCS-15 [73]. In our analysis of the genomes of the 57 isolates from across the globe, TCS-15 was found in 16 of the 57 strains, and was distributed across all serotypes.…”
Section: Resultsmentioning
confidence: 83%
“…The sequence alignment reveals that the MecA protein in S. mutans is highly homologous to those in Streptococcus agalactiae A909 (67% identity), Streptococcus pyogenes M1 GAS (63% identity), and S. thermophilus LMD-9 (57% identity). The MecA proteins are well conserved among S. mutans strains, since all four fully sequenced S. mutans strains, strains UA159, GS-5, NN2025, and LJ23, contain a putative MecA in their genomes (30,(33)(34)(35). In particular, the MecA proteins in S. mutans strains share high levels of conservation at the N-terminal domain (NTD) and C-terminal domain (CTD) with those of S. thermophilus and B. subtilis (24)(25)(26)(27)(28), suggesting that MecA in S. mutans might act as an adaptor protein to interact with its partners to regulate competence and stress response in a manner similar to the proteins in S. thermophilus and B. subtilis (24)(25)(26)(27)(28).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, a similar regulatory mechanism involving sequestration of SigX by a SigX-MecA-ClpC complex has been reported in Streptococcus thermophilus, in which the type I ComRS system primarily regulates the expression of comX for genetic competence (28,29). The S. mutans genome lacks both comW and comK, but it contains all of the genes encoding SigX, MecA, ClpC, and ClpP (30)(31)(32)(33)(34)(35). Whether MecA in S. mutans plays a functional role in the regulation of the SigX activity and competence was unknown.…”
mentioning
confidence: 99%
“…Analysis of the complete sequence from UA159 showed that the six genes encoding LPXTG-anchored proteins are pac, fruA, dexA, gbpC, wapA, and wapE (10), all of which have also been identified in strains NN2025, LJ23, and GS-5 (11)(12)(13). The approximately 190-kDa protein antigen (PA) encoded by pac, which is also known as SpaP, P1, and other designations, is expressed in extremely small amounts in serotype k strains compared with the levels found in strains commonly present in the oral cavity.…”
Section: Nfective Endocarditis (Ie) Is a Life-threatening Disease Fmentioning
confidence: 99%